Purinergic signaling in the male reproductive tract - Belardin, Larissa Berloffa; Brochu, Kéliane; Légaré, Christine; Battistone, Maria Agustina; Breton, Sylvie (Frontiers in Endocrinology, 2022)
Purinergic receptors are ubiquitously expressed throughout the body and they participate in the autocrine and paracrine regulation of cell function during normal physiological and pathophysiological conditions. Extracellular nucleotides activate several types of plasma membrane purinergic receptors that form three distinct families: P1 receptors are activated by adenosine, P2X receptors are activated by ATP, and P2Y receptors are activated by nucleotides including ATP, ADP, UTP, UDP, and UDP-glucose. These specific pharmacological fingerprints and the distinct intracellular signaling pathways they trigger govern a large variety of cellular responses in an organ-specific manner. As such, purinergic signaling regulates several physiological cell functions, including cell proliferation, differentiation and death, smooth muscle contraction, vasodilatation, and transepithelial transport of water, solute, and protons, as well as pathological pathways such as inflammation. While purinergic signaling was first discovered more than 90 years ago, we are just starting to understand how deleterious signals mediated through purinergic receptors may be involved in male infertility. A large fraction of male infertility remains unexplained illustrating our poor understanding of male reproductive health. Purinergic signaling plays a variety of physiological and pathophysiological roles in the male reproductive system, but our knowledge in this context remains limited. This review focuses on the distribution of purinergic receptors in the testis, epididymis, and vas deferens, and their role in the establishment and maintenance of male fertility.